2009
DOI: 10.7202/038325ar
|View full text |Cite
|
Sign up to set email alerts
|

Modélisation dynamique du comportement des métaux lourds dans des stations d’épuration

Abstract: Le but de ce travail était de développer un modèle permettant de décrire le comportement des métaux lourds, en plus des polluants traditionnels, dans une station d’épuration par boues activées et pouvant être utilisé pour sa conception et son optimisation. Le modèle, qui considère la sorption des métaux lourds sur des matières en suspension comme processus réactionnel, a été évalué à partir de données recueillies durant dix jours dans un système réel de traitement par boues activées. Les résultats démontrent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Sorption and volatilization consist in a transfer of the micropollutant, based on equilibrium mechanisms, between two compartments, dissolved-solid and dissolved-gas compartments, respectively, whereas biodegradation implies an elimination of the micropollutant from the dissolved or solid compartment (Pomiès et al 2013). So, among these three mechanisms, sorption is the only that is usually considered for metals removal (Pomiès et al 2013;Cloutier et al 2009;Wang et al 2006), which is of course a simplification and certainly not applicable to some metals (As, Hg) that may form volatile compounds when in contact with organic matter. Parker et al (1994) concluded that partitioning due to precipitation is another mechanism that must be considered, particularly for metals with low solubility.…”
Section: Removal Mechanisms Partitioning and Mass Balances For Metalmentioning
confidence: 99%
See 2 more Smart Citations
“…Sorption and volatilization consist in a transfer of the micropollutant, based on equilibrium mechanisms, between two compartments, dissolved-solid and dissolved-gas compartments, respectively, whereas biodegradation implies an elimination of the micropollutant from the dissolved or solid compartment (Pomiès et al 2013). So, among these three mechanisms, sorption is the only that is usually considered for metals removal (Pomiès et al 2013;Cloutier et al 2009;Wang et al 2006), which is of course a simplification and certainly not applicable to some metals (As, Hg) that may form volatile compounds when in contact with organic matter. Parker et al (1994) concluded that partitioning due to precipitation is another mechanism that must be considered, particularly for metals with low solubility.…”
Section: Removal Mechanisms Partitioning and Mass Balances For Metalmentioning
confidence: 99%
“…AnD-anaerobic digester, ASP-activated sludge process, Df-disinfection, Dw-dewatering, Gr-grit removal, Q-flow rate, FEf-final effluent, FSg-final sludge, RAS-returned activated sludge, RW-raw wastewater, RSLAn-returned sludge liquor from the anaerobic digester, RSLTh-returned sludge liquor from sludge thickening, PS-primary settler, PSEf-primary settler effluent, PSg-primary sludge, Scr-screening, SSg-secondary sludge, SSolids-suspended solids, SS-secondary settler, Th-thickening metals, although some research has been developed in this area, with a limited number of models reported. Based on scientific literature and expert knowledge, Pomiès et al (2013), in a recent comprehensive review on the removal of micropollutants in biological wastewater treatment, identified two main references concerning metals modelling in WWTPs, both of them patented and marketed: Toxchem model (Parker et al 1994) and WEST model (Cloutier et al 2009;Vanhooren et al 2003). Both models consider similar mass balance equations, but the first is defined as a static model, meaning that it only simulates permanent regime, while WEST is a dynamic model, meaning that it is more adapted to account to the temporal variations of micropollutant concentrations in WWTPs.…”
Section: Modelling Of Metals Behaviour In Wwtpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloutier et al [63] modelled the removal of particulate heavy metals during primary settling under the assumption that removal of particle-bound heavy metals is relative to the removal of SS in the settler (removal efficiency thus being the same for all heavy metals). The model also assumes that dissolved heavy metals are removed only by mass flow of dissolved heavy metals with sludge, i.e., the concentration of dissolved heavy metals in primary settler overflow is the same as in primary settler influent.…”
Section: Partitioning Constants and Modeling Of Heavy Metal Speciation And Removalmentioning
confidence: 99%